The Case of Acute Steroid-Induced Myopathy in the Patient with Autoimmune Thrombocytopenia - N. T. Vatutin; G. A. Ignatenko; G. G. Taradin; I. V. Kanisheva; M. R. Shajmurzin (Архивъ внутренней медицины)
The article concerns one of the common adverse effects during treatment — steroid myopathy. The information about pathogenic specifics of myopathy development in administration of glucocorticoids, the most typical clinical manifestations are described, and results diagnostic methods with estimation of a role of enzyme level evaluation, electromyography, ultrasound study of the muscle tissue, computer and magnetic resonance tomography. There is description of muscle weakness development in 49-year old woman who has been receiving methylprednisolone 88 mg/day due to revealed thrombocytopenia. One week after the treatment was started the patient experienced onset and progression of muscle weakness limiting her motion and self-maintenance. After performing of investigation including electromyography steroid genesis of myopathy was suggested. The patient’s condition began to improve after disc ontinuation of glucocorticoids and administration of calcium supplements, vitamin D, and anabolics, and the patient was discharged.